SDG16 – Peace and Justice : Challenges, Actions and the Way Forward - Radović, Vesela, author 646686; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2019)
This book details how interested parties can, must and are getting ahead of the curve to promote peace, provide access to justice and build accountable institutions for all. It envisions a hopeful future in which the impacts of SDG16 are likely to be far more positive, transformational, and visible much more quickly, than we might have imagined.